2016
DOI: 10.1016/j.bbrc.2016.09.071
|View full text |Cite
|
Sign up to set email alerts
|

Differential phosphorylation-based regulation of αB-crystallin chaperone activity for multipass transmembrane proteins

Abstract: We have previously shown that αB-crystallin (CRYAB), a small heat shock protein (sHsp) that prevents irreversible aggregation of unfolded protein by an ATP-independent chaperone activity, plays a pivotal role in the biogenesis of multipass transmembrane proteins (TMPs) assisting their folding from the cytosolic side of the endoplasmic reticulum (ER) (D'Agostino et al., 2013). Here we present evidence, based on phosphomimetic substitutions, that the three phosphorytable serine residues at position 19, 45 and 59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…Ser19 and ser45 have strong inhibitory effects alone or in combination, while ser59 does not have an inhibitory effect, and could offset the inhibitory effect of monophosphorimide in ser19 and ser45. The phosphorylation of ser19 and ser45 alone or in combination resulted in a significant decrease in cryAB chaperone activity, whereas the monophosphorimide in ser59 had no such effect [ 43 ]. After being pretreated with rosamultin, the level of cryAB decreased, and the level of pCryAB S59 expression increased.…”
Section: Discussionmentioning
confidence: 99%
“…Ser19 and ser45 have strong inhibitory effects alone or in combination, while ser59 does not have an inhibitory effect, and could offset the inhibitory effect of monophosphorimide in ser19 and ser45. The phosphorylation of ser19 and ser45 alone or in combination resulted in a significant decrease in cryAB chaperone activity, whereas the monophosphorimide in ser59 had no such effect [ 43 ]. After being pretreated with rosamultin, the level of cryAB decreased, and the level of pCryAB S59 expression increased.…”
Section: Discussionmentioning
confidence: 99%
“…αB-crystallin has proved to play a crucial role in the biogenesis of multipass transmembrane proteins (TMPs) by assisting their folding from the cytosolic face of the endoplasmic reticulum (ER) [19]. Furthermore, Ciano et al (2016) established that phosphorylation of serine, resident at position 59, finely regulates the chaperone activity of HspB5 with studied TMPs [20]. Recent studies demonstrated the competence of HspB5 to interact with membrane channels.…”
Section: State Of Knowledgementioning
confidence: 99%
“…However, a second hypothesis emerges from what occurs with two TMPs (Frizzled 4 receptor and ATP7B) similar to the multi-spanned transmembrane CFTR where HspB5 rescues the mutated TMPs. Thus, HspB5 could rescue F508del-CFTR rather than promoting its degradation [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…HspB5 counteracts aggregation and rescues proper localization of mutated Frizzled 4 receptor and ATP7B, two mutated TMPs associated, respectively, with familial exudative vitreoretinopathy and Wilson's disease [18]. This beneficial effect on the misfolded TMPs was demonstrated to be regulated by HspB5 phosphorylation status [19]. In view of these data, we decided to evaluate if HspB5 could facilitate misfolded CFTR degradation, much like HspB1 and HspB4, or in contrast, promotes proper localization of mutated CFTR, as reported with other TMPs.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation